2012
DOI: 10.1007/s10596-012-9323-1
|View full text |Cite
|
Sign up to set email alerts
|

A simultaneous perturbation stochastic approximation algorithm for coupled well placement and control optimization under geologic uncertainty

Abstract: Development of subsurface energy and environmental resources can be improved by tuning important decision variables such as well locations and operating rates to optimize a desired performance metric. Optimal well locations in a discretized reservoir model are typically identified by solving an integer programming problem while identification of optimal well settings (controls) is formulated as a continuous optimization problem. In general, however, the decision variables in field development optimization can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
71
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(71 citation statements)
references
References 31 publications
0
71
0
Order By: Relevance
“…In this study we used a reactive control based performance to rank and choose the set of models. Li et al (2012), using the SPSA technique to approximate a gradient, suggested to randomly select a subset of models at every iteration of the optimization, instead of using an a-priori chosen subset of models. With this randomly chosen set, similar to the selected models approach, individual gradients are estimated to estimate a single robust gradient.…”
Section: Different Gradient Formulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study we used a reactive control based performance to rank and choose the set of models. Li et al (2012), using the SPSA technique to approximate a gradient, suggested to randomly select a subset of models at every iteration of the optimization, instead of using an a-priori chosen subset of models. With this randomly chosen set, similar to the selected models approach, individual gradients are estimated to estimate a single robust gradient.…”
Section: Different Gradient Formulationsmentioning
confidence: 99%
“…Additionally, Raniolo et al (2013) and Li et al (2012), have investigated the applicability of approximate gradient techniques for life-cycle robust water flooding optimization while Yang et al (2011) applied the robust optimization principle to a Steam-Assisted Gravity Drainage (SAGD) application. Yasari et al 2013, Pajonk et al 2011 and Awotunde and Sibaweihi (2011) have investigated the applicability of robust multi-objective optimization using evolutionary algorithms for well control and well placement optimization with objectives varying from economic criteria to voidage replacement ratio and cumulative production volumes.…”
Section: Introductionmentioning
confidence: 99%
“…For the use in robust optimization, see van Essen et al (2009); for a general overview, see Jansen (2011). Alternative, less codeintrusive, robust methods use approximate gradient and/or stochastic methods (Chen et al 2009;Chen and Oliver, 2010;Li et al 2013;Fonseca et al 2015Fonseca et al , 2016 or 'non-classical' methods such as, e.g., streamline methods (Alhutali et al 2008), evolutionary strategies (Pajonk et al 2011), or polynomial chaos expansions in combination with response surfaces (Babaei et al 2015), with further references given in Echeverrıa Ciaurri et al (2011).…”
Section: Application Case Reservoir Engineering -Long-term Reservoir mentioning
confidence: 99%
“…For instance, particle swarm optimization (PSO) [17] and the simultaneous perturbation stochastic approximation (SPSA) [4,24] were introduced to accelerate the convergence of the iterative process towards an optimal solution. The SPSA was also applied to an optimal well-placement problem under geologic uncertainty [18], where the optimal solution was the maximum over an average of a statistical ensemble of size 100 reflecting uncertainty in permeability. It was observed that accounting for geologic uncertainty in this manner had a noticeable effect on the optimal wellplacement.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, both robust optimization [13,28], involving a combination of mean and variance, risk-based optimization involving probabilities of exceedance [2], conditional value-at-risk (CVaRO) [8] dealing with risks associated with low returns, and utility functions [16] have been considered. Several recent studies dealing with optimal well-placement have stressed the value of joint location/control optimization whereby both the location of the wells and production strategy over some time horizon are simultaneously optimized [5,6,18,28,29]. Clearly, in such cases, the computational aspects of the optimization problem are significantly more challenging, specially when accounting for uncertainties in geology, investment, and pricing.…”
Section: Introductionmentioning
confidence: 99%